Structure–Resistance Relationships: Interrogating Antiseptic Resistance in Bacteria with Multicationic Quaternary Ammonium Dyes. (30th March 2016) - Forman, Megan E.; Fletcher, Madison H.; Jennings, Megan C.; Duggan, Stephanie M.; Minbiole, Kevin P. C.; Wuest, William M.
Abstract: Bacterial resistance toward commonly used biocides is a widespread yet underappreciated problem, one which needs not only a deeper understanding of the mechanisms by which resistance proliferates, but also means for mitigation. To advance our understanding of this issue, we recognized a polyaromatic structural core analogous to activators of QacR, a negative transcriptional regulator of the efflux pump QacA, and envisioned a series of quaternary ammonium compounds (QACs) based on this motif. Using commercially available dye scaffolds, we synthesized and evaluated the antimicrobial activity of 52 novel QACs bearing 1–3 quaternary ammonium centers. Striking differences in antimicrobial activity against bacteria bearing QAC resistance genes have been observed, with up to a 125‐fold increase in minimum inhibitory concentration (MIC) for select structures against bacteria known to bear efflux pumps. Based on these findings, general trends in structure–resistance relationships have been identified, laying the groundwork for future mechanistic studies. Abstract : The SRRs of QACs ! We report the synthesis and antimicrobial activity of a series of mono‐ and multi‐quaternary ammonium compounds (QACs) based on commercially available dye scaffolds to probe their "structure–resistance relationship". MonoQACs demonstrated increased MIC values against Gram‐positive strains known to contain resistance genes, including those previously shown to efflux QACs. In contrast, our multiQACs retained activity against such bacteria as well as Gram‐negative strains.